Moderasi Beragama dan Multikulturalisme Sebagai Transformasi Pendidikan Masa Depan - Ulpa Reni; Syarifuddin Ondeng; Afifuddin Harisah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic education plays a strategic role in shaping a comprehensive, moderate, and contextual religious understanding for the Muslim generation. However, amid the rapid current of globalization, Islamic education is challenged to undertake fundamental transformation through the integration of religious moderation (wasathiyah) and multiculturalism. This article aims to examine the basic concepts of Islamic education, its transformational dynamics from the classical era to the global era, and the urgency of integrating religious moderation and multiculturalism into the contemporary Islamic education system. This research employs a qualitative approach using a library research method. Data were collected from primary sources — key literature in Islamic education thought — and secondary sources including relevant scholarly journals and research articles. Data collection was conducted through documentation, while data analysis employed content analysis. The findings indicate that the transformation of Islamic education encompasses four historical phases. Religious moderation grounded in the four pillars of wasathiyah — tawassuth, tawazun, i'tidal, and tasamuh — is proven capable of serving as the foundation for inclusive and anti-extremism education. Multiculturalism from an Islamic perspective is positioned as a positive potential consistent with the mission of rahmatan lil alamin. The future vision of Islamic education rests on the synergistic integration of faith, knowledge, and technology. In conclusion, the transformation of Islamic education toward moderation and multiculturalism is not merely a reform agenda, but a historical and theological imperative in building a moderate, critical, and globally minded Muslim generation.